Development of Multicultural Education Through Sufism's Value of Satlogi Santri in Pesantren - Islam, Muhammad Hifdil; Baihaqy Yussof, Mohammad Hilmy (Letiges, 2024)
This research explores the development of multicultural education through sufism values ??in Islamic boarding schools. Santri satlogy refers to the philosophical values ??in Islamic boarding schools, consisting of sufism values that emphasize the importance of tolerance, inclusiveness and respect for diversity, which are crucial components in this educational approach. This research uses a qualitative case study design using interviews, observation and document analysis to collect data at the Zainul Hasan Genggong Islamic Boarding School. Then, Miles and Huberman were used to analyze the data. Research findings reveal that the value of sufism and the santri satlogy as a catalyst for the development of multicultural education plays a vital role in advancing multicultural education. Santri satlogy can incorporate Sufi thoughts to foster a more comprehensive and spiritually oriented education. By emphasising the values ??of courtesy, steadfastness or istiqomah or perseverance, advice, taqwallah, ridhallah, and sincerity lillahi ta'ala can help students develop the critical skills necessary for success in this life and the next. These principles can foster empathy and tolerance towards others, essential for promoting harmony and peace in multicultural communities. Limitations are shown on the site regarding how the sufism values ??contained in the santri satlogy can develop multicultural education in Islamic boarding schools. The injection of sufism values ??into the santri satlogy enables the students to develop a deeper understanding of Islamic teachings and local culture while promoting tolerance and respect for diversity. Sufism values ??have been integrated into Islamic boarding school educational practices, resulting in a more inclusive and just learning environment. The study concluded that santri satlogy as a sufism value has the potential to contribute to the development of multicultural education in other Islamic educational institutions.